Pneumococcal hyaluronidase: a product of enzyme in normal human flora - Ahmad Yusof @ Hanafi, Hanani; Mohd Desa, Mohd Nasir; Masri, Siti Norbaya; Osman, Malina; Jamal, Farida (2016)
Hyaluronidase degrades hyaluronan or hyaluronic acid (HA), a major component of extracellular matrix in human connective tissues. Among three types of hyaluronidase family members, hyaluroglucosaminidase which is extracted from vertebrate testes has been widely used in various medical or cosmetically-related procedures such as ophthalmic surgery and dermatosurgery. Animal-based proteins are often associated with the issue of halal status due either to their source or the production process. Bacteria can be an alternative source of enzyme and protein as no halal issues may be involved as in the case of animal products. Bacterial hyaluronidase has been reported to be produced by various species of microorganisms, including Streptococcus pneumoniae. Most previous studies reported pathogenic pneumococci as highly active producers of hyaluronidase, while its production by normal flora pneumococci has yet to be intensively explored. The present study attempted to compare hyaluronidase activity between normal flora and pathogenic pneumococci. A total of fifteen (n=15) pathogenic pneumococci isolated from blood of invasive pneumococcal disease patient and eleven (n=11) normal flora pneumococci isolated from anterior nares of healthy individuals were screened for hyaluronidase activity using HA agar plate and HA turbidity reduction assay. All pneumococci strains produced hyaluronidase, with higher enzymatic activity in normal flora pneumococci (p = 0.024). This finding suggests that normal flora could be a selected and studied for large scale production of hyaluronidase which more likely to be a syariah compliant and halal source of the enzyme.